2012
DOI: 10.1088/0954-3899/40/1/015006
|View full text |Cite
|
Sign up to set email alerts
|

Neutron production from the fracture of piezoelectric rocks

Abstract: A theoretical explanation is provided for the experimental evidence that fracturing piezoelectric rocks produces neutrons. The elastic energy micro-crack production ultimately yields the macroscopic fracture. The mechanical energy is converted by the piezoelectric effect into electric field energy. The electric field energy decays via radio frequency (microwave) electric field oscillations. The radio frequency electric fields accelerate the condensed matter electrons which then collide with protons producing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…This excited state of the matter could be a cause of subsequent resonance phenomena of nuclei able to produce neutron bursts. This hypothesis is also confirmed by Widom et al [22,23]. As a matter of fact, the microcracking elastic energy release ultimately yields the acoustic vibrations, which are converted into electromagnetic oscillations.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…This excited state of the matter could be a cause of subsequent resonance phenomena of nuclei able to produce neutron bursts. This hypothesis is also confirmed by Widom et al [22,23]. As a matter of fact, the microcracking elastic energy release ultimately yields the acoustic vibrations, which are converted into electromagnetic oscillations.…”
Section: Introductionsupporting
confidence: 54%
“…As a matter of fact, the microcracking elastic energy release ultimately yields the acoustic vibrations, which are converted into electromagnetic oscillations. The electromagnetic waves, generated during microcracking, accelerate the condensed matter electrons which then collide with protons producing neutrons and neutrinos [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Energy Dispersive X-ray Spectroscopy (EDS), performed on samples coming from the Luserna stone specimens used in the preliminary experiments [1][2][3], show that on the fracture surfaces a considerable reduction in the iron content (*25 %) is very consistently counterbalanced by an increment in Al, Si, and Mg concentrations [4]. A theoretical explanation about piezonuclear fission reactions has been provided very recently [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The EMR emissions in non-metallic materials have also been correlated with acoustic emissions, e. g. [20 -23]. Carpinteri et al [24,25] and Widom et al [26] reported piezo-nuclearneutron emissions alongwithEMR and acoustic emissions duringc ompressive failure of nonmetallic brittle materials. Acoustic emission during tensile testingofmagnesium alloysheetshas been measured in order to investigate the influence of microstructure and texture on the deformation behaviour [27].S tudy of acoustic emission under compression in alloys may help in texture evolution during plastic deformation [28].…”
Section: Introductionmentioning
confidence: 99%